LEAN maintenance model based on change management allowing the reduction of delays in the production line of textile SMEs in Peru - Arrascue-Hernandez, G. (2020)
This article examines the problem of production line delays in a textile small- and medium-sized enterprise (SME) that produces polyester fibre from recycled bottles, based on orders. Factors that have resulted in production line delays include prolonged unscheduled maintenance time, and preparations and adjustments prior to operating the equipment. To address the problem, a model was developed applying lean manufacturing tools through change management, with the aim of increasing equipment availability and useful life. To validate the model, a pilot was developed to determine how the increase in equipment availability helps reduce delays in the production line, which eventually improves completion of customer orders.